The Current Studies of Education for a Traditional and Complementary Medicine in Malaysia - Yun Jin Kim PhD (SAGE Publishing, 2017)
The aim of this study is to understand the current tradition and complementary medicine (T&CM) education in Malaysia. We referred to literature regarding to traditional medicine education in Malaysia, and collected the information via website or interview with faculty of T&CM in universities/colleges and Division of T&CM, Ministry of Health, Malaysia. T&CM education in Malaysia has been following China's T&CM systems for 50 years. Currently, Division of T&CM, Ministry of Health; and Ministry of Higher Education has approved 11 institutions to offer T&CM education. Students may major in Chinese herbal medicine, acupuncture, or other T&CM subjects. Generally, clinical training programs in China, Taiwan, or Australia include substantial proportion of clinical training. We report on the general information of T&CM education in Malaysia. This result would be the first-stage information for the establishment of a strategy regarding the enhancement of T&CM education in Malaysia.